Is Business Planning Useful for Entrepreneurs? A Review and Recommendations - Hiroko Nakajima; Tomoki Sekiguchi (Businesses)
Whether or not business planning is useful for entrepreneurs is a critical question both academically and practically. While some studies suggest that structured business planning enhances business performance, others argue that it may be unnecessary or even counterproductive in uncertain environments. This lack of consensus creates a gap between academic research and practical application, leaving entrepreneurs without clear guidance on when and how to engage in business planning and what impact it may have. To address this issue, we conducted an integrative literature review on the effectiveness of business planning in entrepreneurship. The results of our review suggest that business planning is generally effective, and we categorize its effects into three aspects: (1) economic effects, such as start-ups’ improved sustainability and profitability; (2) external and symbolic effects for stakeholders, including enhanced decision-making for external funding, trust building, vision legitimization, and stakeholder engagement; and (3) internal and psychological effects, such as improved decision-making, cognitive enhancement, and flexibility for entrepreneurs. This article also highlights the gaps in the literature, particularly regarding the relationship between business planning and factors such as time, environmental conditions, feedback loops, entrepreneurial passion, and psychological ownership. To fully leverage the benefits of business planning, we propose six evidence-based recommendations to guide entrepreneurs in effectively utilizing this critical tool.